Мир растений: рассказы о кофе, лилиях, пшенице и пальмах / А. Смирнов - Смирнов Алексей Всеволодович (Эврика, 1981)
Экземпляры: Абоонемент (20180820) / Инвентарный номер: 2022 / Цена: 2.30 / Сис.шифр: 28.5 / Авт.знак: С 50 / ГРНТИ: 34 / ББК: 28.592